Dissolving Microneedle-Based Cascade-Activation Nanoplatform for Enhanced Photodynamic Therapy of Skin Cancer - Ma J; Tai Z; Li Y; Li Y; Wang J; Zhou T; Shen M; Xin R; Shen C; Zhu Q; Chen Z (International Journal of Nanomedicine, 2024)
Jinyuan Ma,1,2,* Zongguang Tai,1,2,* Ying Li,1,2,* Yang Li,3 Jiandong Wang,1,2 Tao Zhou,1,2 Min Shen,1,2 Rujuan Xin,1,2 Cuie Shen,1,2 Quangang Zhu,1,2 Zhongjian Chen1,2 1Shanghai Skin Disease Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2Shanghai Engineering Research Center for Topical Chinese Medicine, Shanghai, People’s Republic of China; 3CAS Key Laboratory of Design and Assembly of Functional Nanostructures, Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quangang Zhu; Zhongjian Chen, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, 1278 Baode Road, Shanghai, 200443, People’s Republic of China, Tel/Fax +86 21 36803155 ; +86 21 36803007, Email qgzhu@126.com; aajian818@163.comPurpose: Photodynamic therapy (PDT) has been an attractive strategy for skin tumor treatment. However, the hypoxic microenvironment of solid tumors and further O2 consumption during PDT would diminish its therapeutic effect. Herein, we developed a strategy using the combination of PDT and hypoxia-activated bioreductive drug tirapazamine (TPZ).Methods: TPZ was linked to DSPE-PEG-NHS forming DSPE-PEG-TPZ to solve leakage of water-soluble TPZ and serve as an antitumor agent and monomer molecule further forming the micellar. Chlorin e6 (Ce6) was loaded in DSPE-PEG-TPZ forming DSPE-PEG-TPZ@Ce6 (DPTC). To further improve tumor infiltration and accumulation, hyaluronic acid was adopted to make DPTC-containing microneedles (DPTC-MNs).Results: Both in vitro and in vivo studies consistently demonstrated the synergistic antitumor effect of photodynamic therapy and TPZ achieved by DPTC-MNs. With laser irradiation, overexpressions of PDT tolerance factors NQO1 and HIF-1α were inhibited by this PDT process.Conclusion: The synergistic effect of PDT and TPZ significantly improved the performance of DPTC-MNs in the treatment of melanoma and cutaneous squamous cell carcinoma and has good biocompatibility.Keywords: photodynamic therapy, hypoxia activation, combination therapy, PDT enhancement